Promoting English Oral Communication and Higher-Order Thinking in Taiwanese ESL Students through the Use of Knowledge Visualization Techniques. Issue 3 (June 2014) - Wang, Ya-Huei; Liao, Hung-Chang
The study examined whether the students using concept mapping in a Freshman English course would improve English oral communication proficiency, higher-order thinking, and perception of abilities. A quasi-experimental design, lasting for 12 weeks, was administered to an experimental group (21 students) and a control group (20 students). The experimental group had significantly better performance on all measures. Concept mapping was effective in improving college students' English oral communication, higher-order thinking, and perception of abilities development.